Depth-resolved carbon dioxide and methane concentrations in 522 lakes, ponds, and reservoirs worldwide - Rabaey, Joseph S.; Lewis, Abigail S. L.; Attermeyer, Katrin; Aurich, Patrick; Bansal, Sheel; Bartosiewicz, Maciej; Bertolet, Brittni L.; Bussmann, Ingeborg; Cadieux, Sarah B.; Calamita, Elisa; Capelli, Camilla; Carey, Cayelan C.; et al. (Springer Nature, 2026)
Lakes, ponds, and reservoirs (hereafter: “lakes”) are important sources of the greenhouse gases carbon dioxide (CO2) and methane (CH4). Emissions of CO2 and CH4 from lakes are regulated in part by in-lake processes, including the production and storage of gases in the lower parts of the water column (bottom waters). However, while substantial efforts have been made to improve estimates of greenhouse gas emissions from lakes, limited data on gas concentrations along depth profiles have prevented the incorporation of bottom-water processes in global emission estimates. Here, we present GHG-depths: the largest existing dataset of depth-profile CO2 and CH4 measurements worldwide, including 522 lakes across 38 countries and all seven continents. These data include contributions from 45 research teams and 56 published studies, totaling 2558 discrete sampling events. As global change continues to alter biogeochemical cycling in lakes, these data can help improve mechanistic models to better predict greenhouse gas production and emission from lakes worldwide.
Keywords: carbon cycle; limnology